Answer:
A = 4; B = -1 ; C = -29
Step-by-step explanation:
y = 4(x + 6) + 5
y = 4x + 24 +5
y = 4x + 29
Standard form: Ax + By = C
4x - y = -29
Answer:
The Answer is 47
Step-by-step explanation:
Because you do A squared plus B squared equals C squared and Squared is just multiplying both by two.
Answer:
15, 6 and - 3
Step-by-step explanation:
Given x - y = 3 , then
(a)
5(x - y) = 5(3) = 15
(b)
2x - 2y ← factor out 2 from each term
= 2(x - y) = 2(3) = 6
(c)
y - x ← factor out - 1 from each term
= - 1(x - y) = - 1(3) = - 3
If we say dilation, we mean to say that the endpoints or the corners of the polygon is move by the number of scale factors away from the original point. Unfortunately, you missed to give here an illustration of both quadrilaterals, it would have been easy for us to answer this item should we have been given with the dimensions.